Academe-industry partnerships models for enhancing human capital development - Suarez, Eleanor A. Imbang; Sibal, Jorge V.; Asuncion, Ronahlee A.; Atienza, Theresita V.; Yuzon, Isagani A.F. (2010)
Academe-industry partnerships (AIPs) aim to improve the performance of higher education institution (HEIs) by producing competent and able graduates in order to increase their employability in the formal and informal sectors of the economy. The study described and assessed the effectiveness of the current AIP models in four (4) HEIs, namely: Polytechnic University of the Philippines (PUP), University of the Philippines Diliman (UPD), Our Lady of Fatima University(OLFU) and University of Perpetual Help System (UPHS),and their industry partners in Metro Manila in terms of developing human capital to address the problem of job skills mismatch and enhance employability of their respective graduates.The four HEIs entered into a partnership scheme with industry for the following reasons: 1) to increase opportunities of students through on-the-job training(OJT) program with industries in order to improve their knowledge and skills; 2) to enable industries to provide inputs that could improve the school's curricula; 3) to help the schools in infrastructure and facilities improvement and in faculty development programs or research. The study also found out that majority of the tie-ups between schools and companies particularly in the conduct of the OJT program for students were not covered by written agreements. AIPs in private and public HEIs were operated in the same manner. UPD made the most out of academe-industry partnerships among the four HEI respondents. The UPD had made the most number of tie-ups with industry in terms of programs in scholarship, student services, curricular reforms, OJT, improvement in infrastructure and facilities, faculty development and research. The four selected HEIs were benefited mostly by curricular enhancement and followed by faculty development programs. In general, curricular reforms were prevalent among the HEIs. Their respective curricula were aligned with the current industry standards or demands which enhanced the employability of their graduates. It is recommended that HEIs should assess and improve their current AIPs and explore wider and varied partnerships with other companies.
"July 2010."
Thesis (M.Industrial Relations)--University of the Philippines Diliman.
Keywords: Human capital; Education industry -- Social aspects; Employer-supported higher education